2013
DOI: 10.1002/jsfa.6037
|View full text |Cite
|
Sign up to set email alerts
|

Influence of linseed variety on fatty acid profile in cow's milk

Abstract: Linseed variety significantly influenced the lipid fraction level and the basic chemical composition of cow's milk. Linseed variety should therefore be taken into consideration in subsequent experiments in addition to the quantity and physical form of linseed. The results showed that the use of a diet supplemented with linseed, especially the Szafir variety, was effective in reducing saturation, atherogenic and thrombogenic indices, yielding benefits for consumers by improving the nutritional quality of cow's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 19 publications
1
28
0
1
Order By: Relevance
“…Many factors affect the FA composition of bovine milk, including season (Sakowski and others ), parity (Puppel and others ), access to fresh grazing (Kuczyńska ; Kuczyńska and others ), grazing sward type (Hauswirth and other ), silage type (Dewhurst and others ), polymorphic forms of β‐lactoglobuline (Puppel and others ) or fish oil, and linseed supplementation (Puppel and others , ). Our study showed that the content of monounsaturated fatty acids (MUFA) in milk fat was dependent largely on the concentration of PUFA, and to a lesser extent on the supply of MUFA (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many factors affect the FA composition of bovine milk, including season (Sakowski and others ), parity (Puppel and others ), access to fresh grazing (Kuczyńska ; Kuczyńska and others ), grazing sward type (Hauswirth and other ), silage type (Dewhurst and others ), polymorphic forms of β‐lactoglobuline (Puppel and others ) or fish oil, and linseed supplementation (Puppel and others , ). Our study showed that the content of monounsaturated fatty acids (MUFA) in milk fat was dependent largely on the concentration of PUFA, and to a lesser extent on the supply of MUFA (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Identification with fatty acid standards and quantitative determination of individual fatty acids in crude fat were conducted using an Agilent 7890A gas chromatograph with HP ChemStation software (Agilent Technologies), a flame ionization detector and a Varian Select FAME column (100 m length, 0.25 mm dia, 0.25 μm film thickness; Varian/Agilent Technologies). The analysis involved a programmed run with temperature ramps under the conditions and temperatures described by Puppel and others (). Each peak was identified and quantified using pure methyl ester standards (PUFA no.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…High oxidative stress is common in organs and tissues with high metabolic and energy demands, including skeletal and heart muscle, liver and blood cells . Milk composition can be altered by the feeding regime . Antioxidants can be transferred either directly from the feed to the milk, or indirectly, diet supplements cows' milk .…”
Section: Introductionmentioning
confidence: 99%
“…For above reasons, public health guidelines in most developed countries have recommended population-wide reduction in saturated and trans FA and an increase in 18:3n-3, 20:5n-3, and 22:6n-3 in the human food chain to decrease the incidence of chronic disease (WHO, 2003). Although increasing the proportion of polyunsaturated fatty acids (PUFA) in milk is limited due to extensive biohydrogenation of these FA in the rumen, supplementing linseed to dairy cattle increased the proportion of cis -9, trans -11-18:2 ( c 9, t 11 CLA) and n-3 FA, particularly linolenic acid, EPA and DHA in milk (Glasser et al, 2008, Lerch et al, 2012; Puppel et al, 2013). The objective of this study was to characterize milk FA composition responses to different forms of dietary linseed supplements in lactating dairy cows fed a diet based on grass silage.…”
Section: Introductionmentioning
confidence: 99%